The Role of MTs N 3 Surabaya City in Building Religious Moderation Culture: Analysis of Inclusive and Child-Friendly Education Models - Asmiati, Asmiati; Atmaja, Dwi; Mahmudah, Lilik; Kholiq, Abdul; Widyanto, Priyo Bagus (Annpublisher, 2025)
Backgrounds. As educational institutions with Islamic characteristics, madrasahs play unique roles and bear special responsibilities in this national project. Madrasahs function not only as institutions for knowledge transfer, but also as centers for character formation and religious understanding of Indonesia's young Muslim generation. Aims. This research conducts an in-depth analysis of the religious moderation culture development model at MTsN 3 Surabaya City, positioned as a pioneer in responding to the national agenda for strengthening religious moderation. Facing challenges of intolerance and radicalism, this madrasah has designed a holistic and systematic program architecture. Methods. Using qualitative analysis methods on institutional publication data and news reports, this study identifies three main strategic pillars: (1) student empowerment as agents of change through the flagship program